1980
DOI: 10.1084/jem.151.3.566
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and communicative interrelations of Ly123 and Ly1 cell sets.

Abstract: In defining the relation ofT-cell sets to one another, the prime task is to determine, for a given pair of cell sets jointly required for a particular function, whether one set is recruited from the other by differentiation (developmental sequence) or whether the relationship is entirely communicative (collaboration or induction).The cell sets Ly123 and Lyl are a case in point. From indirect evidence it has been inferred that Ly123 is the precursor set for Lyl cells that act as helper-effectors (HE) x (Ly 1 :H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 10 publications
(9 reference statements)
2
8
0
Order By: Relevance
“…This situation is reminiscent of previous reports from our laboratory that show that most primary cytotoxic T lymphocyte (CTL) precursors are Lyt-123, whereas most Lyt-23 CTL precursors are memory cells (27,39). These results are also in line with a recent report by Shen et al (40), which revealed primary TH cells to arise primarily from the Lyt-123 T cell pool. Thus, we are presently testing the hypothesis that our frequent T. are primary TH cell precursors, whereas the rare TH are secondary TH cell precursors or memory cells.…”
Section: The Methods For Analyzing T Cell Diversity Presented In This supporting
confidence: 89%
“…This situation is reminiscent of previous reports from our laboratory that show that most primary cytotoxic T lymphocyte (CTL) precursors are Lyt-123, whereas most Lyt-23 CTL precursors are memory cells (27,39). These results are also in line with a recent report by Shen et al (40), which revealed primary TH cells to arise primarily from the Lyt-123 T cell pool. Thus, we are presently testing the hypothesis that our frequent T. are primary TH cell precursors, whereas the rare TH are secondary TH cell precursors or memory cells.…”
Section: The Methods For Analyzing T Cell Diversity Presented In This supporting
confidence: 89%
“…We have, however, examined two other functional Ly-1 subsets which, like the Ly-1 help-associated cell described here, are Qa-l+:IJ+: the Ly-1 feedback suppression inducer (FBSI) and the Ly-1 subset that induces the generation of Ly-1 :HE from Ly-i23 precursors (10,15,18,19,37). These cells are distinguished functionally by the mode in which they are assayed, their requisite cell interactions, and their precursor and inducer requirements, but have not as yet been distinguished phenotypically (1,10,15,16,18,19,(33)(34)(35)(36)(37). Whether these functional subsets involve the same or different populations capable of diverse inducer functions remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is also in line with previous results showing that primary and secondary CTLP, when activated in bulk cultures, are Lyt-1 "*"2"' " and Lyt-1 "2"'', respectively (Simon & Abenhard 1980. Moreover, primary and secondary helper T cell precursors have been typed as Lyt-1 "''2''" and Lyt-1 "'"2", respectively (Shen et al 1980). If this conclusion were applied to the data in Figure 1 and Table I, it appears that for weak antigens such as H-Y there is a lack of memory populations, whereas for strong antigens one or 2 memory populations are present, perhaps resulting from natural exposure to cross-reactive antigens.…”
Section: Distinction Of Virgin and Memory T Cells Frequent And Rate mentioning
confidence: 99%